The Peri‐procedural Use of Dabigatran in Patients Undergoing Left Atrial Ablation for Atrial Fibrillation. Issue 5 (October 2014) - Somani, Riyaz; Mohajer, Kiarash; Haley, Charlotte; Simpson, Christopher S.; Abdollah, Hoshiar; Baranchuk, Adrian; Redfearn, Damian P.; Michael, Kevin
Summary Introduction Pulmonary vein isolation is an effective strategy in patients with atrial fibrillation (AF). The peri‐procedural use of anticoagulation is routinely employed to reduce thromboembolic risk. Aims/Methods The aim of this study was to compare the use of Dabigatran to the other 2 strategies involving the use of Warfarin. Single centre observational study comparing 3 anticoagulation strategies: Group 1 consisted of patients maintained on Warfarin (5.15 ± 2.52 mg) with a therapeutic INR of 2–3. Group 2 comprised patients initially treated with Warfarin (6.98 ± 3.17 mg), which was discontinued 1 week prior to LA ablation, during which time patients were bridged with a therapeutic dose of Dalteparin. Group 3 included patients anticoagulated with Dabigatran (40 patients received 150 mg BID, 3 patients received 110 mg BID), which was discontinued 24–30 h prior to the procedure. Results A total of 207 patients were included in the study. There were no significant differences in age, sex, LA volume, CHADS2 score or proportion of patients with persistent AF. There were no significant differences in the number of patients with intra‐cardiac thrombus found at TOE (Group 1: 2.3% vs. Group 2: 1.5% vs. Group 3: 0%; P = 0.37). Furthermore, there were no differences in the rate of groin hematoma (2.2% vs. 1.5% vs. 2.3%; P = 0.8) or the development of pericardial effusion (5.4% vs. 8.8% vs. 2.3%; P = 0.54). No thromboembolic events were seen. Conclusion Peri‐procedural use of Dabigatran during AF ablation procedures is safe, with no significant difference when compared to conventional anticoagulation with either Warfarin bridged with Dalteparin or uninterrupted Warfarin.